The effect of gerontology course on knowledge and attitude towards care of older person among student nurses - Mei Chan, Chong; Ibrahim, Amirah Fatin; Ramoo, Vimala; Jamaludin, Thandar Soe Sumaiyah; Ling, Lee Wan; Chin, Che Chong (2019)
Background Often, nurses have a negative attitude toward older people care and intention to work with older people. It is important to shape the nursing students to inculcate a positive attitude in order to address the demand for older care. The objective of this study was to assess the knowledge and attitudes towards the care of older people among nursing students in Malaysia. Method A quasi-experimental study with control and experimental groups’ pre-test and post-test design was used in this study. Study was conducted among 60 Year Three-degree nursing students in two teaching University in Malaysia. 30 students were assigned to each arm of the study. Students from the control group were thought with conventional teaching-learning method while the intervention group was complement with social media (Whatapp) as an intervention. Pre and post-test were conducted before and after course Result There are significant differences in level of knowledge and attitude between pre and post-test among intervention group with p- value < 0.001 and almost all respondent from the intervention group found caring of older people are rewarded.